2000
DOI: 10.1007/s005350050027
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear cyclin D1 overexpression is a critical event associated with cell proliferation and invasive growth in gallbladder carcinogenesis

Abstract: Cyclin D1 overexpression is remarkably frequent in several human carcinomas and is believed to be a critical event in oncogenesis. We examined cyclin D1 expression, p53 expression, and the Ki-67 labeling index by immunostaining in human gallbladder mucosa in conditions varying from normal to malignant tissue. We also examined K-ras codon 12 mutations in these tissues with a two-step polymerase chain reaction. Nuclear cyclin D1 overexpression was observed in 48% of carcinomas occurring independently of adenoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This is in accordance with the theoretical model where cyclins activate CDKs with an increased net proliferation due to enhanced phosphorylation of G1:S regulatory substrates as the retinoblastoma protein (2-4). Similar observations have been made for cyclin E overexpression and proliferation in various cancers (23,24), whereas cyclin D1 overexpression has been associated with increased proliferation in some but not all tumor types (5,25).…”
Section: Discussionsupporting
confidence: 73%
“…This is in accordance with the theoretical model where cyclins activate CDKs with an increased net proliferation due to enhanced phosphorylation of G1:S regulatory substrates as the retinoblastoma protein (2-4). Similar observations have been made for cyclin E overexpression and proliferation in various cancers (23,24), whereas cyclin D1 overexpression has been associated with increased proliferation in some but not all tumor types (5,25).…”
Section: Discussionsupporting
confidence: 73%
“…This demonstrates that dysregulation of these key proteins may be important already in early carcinogenesis (dysplasia) and that they can serve as markers of both malignancy and premalignancy in gallbladders from patients with PSC. Cyklin D1 is known to be an independent predictor of poor survival in gallbladder cancer [34,35]. The impact on cyclin D1 on prognosis in our study was not possible to evaluate due to the limited number of patients included.…”
Section: Discussionmentioning
confidence: 94%
“…Because other studies have shown cyclin D1 to be a prognostic factor in human cancers (Bova et al 1999, Keum et al 1999, Samejima et al 1999, Cuny et al 2000, Itoi et al 2000, cyclin D1 expression levels were analyzed for correlation with clinical tumour behaviour of these sporadic PETs. Tumours were categorized as benign or malignant based on the presence or absence of hepatic metastases.…”
Section: Cyclin D1 Expression Does Not Correlate With Tumour Aggressimentioning
confidence: 99%
“…Not surprisingly, many human cancers (e.g. breast, parathyroid, head and neck, gastric, oesophageal) have increased cyclin D1 expression (reviewed in Hunter & Pines 1994), and cyclin D1 is a prognostic marker for many cancers (Bova et al 1999, Keum et al 1999, Samejima et al 1999, Cuny et al 2000, Itoi et al 2000. Moreover, forced overexpression of cyclin D1 results in a shortened G1 phase, reduced cellular dependence on exogenous mitogens, and cell transformation (Bodrug et al 1994, Wang et al 1994.…”
Section: Introductionmentioning
confidence: 99%